Anesthetic Implications of Aortic Arch Aneurysm Repair with Deep Hypothermic Circulatory Arrest and Selective Cerebral Perfusion - A Case Report and an Updated Review - Amaral, Caio Levate; Japolino, Katarina Lanza; Delgado, Marina Ayres (Brazilian Journal of Case Reports, 2025)
Deep hypothermic circulatory arrest (DHCA) is a well-established technique offering cerebral protection and optimal surgical conditions for complex cardiovascular and neurological procedures. By cooling the body to 18–20°C, DHCA reduces cerebral metabolic demand, allowing up to 40 minutes of safe circulatory arrest. Extended DHCA is supported by selective antegrade cerebral perfusion (SACP) or retrograde cerebral perfusion (RCP), with SACP preferred for its reliable global oxygenation. Continuous hemodynamic and neurological monitoring, including arterial and central venous pressure, cardiac output, and cerebral oxygenation (NIRS and BIS), is critical for patient safety. This case describes a 62-year-old female undergoing repair of a chronic type I aortic dissection. DHCA with bi-hemispheric SACP was employed, accompanied by hypothermia induction, pharmacological neuroprotection, and tight hemodynamic management. Postoperative outcomes were favorable, with no neurological deficits. Discussion highlights the importance of tailored acid-base, glycemic, and coagulation management strategies. Pharmacological agents, such as barbiturates and corticosteroids, show promise but require further evidence. Combining advanced monitoring techniques enhances safety and outcomes, emphasizing the need for individualized protocols to optimize DHCA efficacy and minimize complications. This case describes a 62-year-old female undergoing repair of a chronic type I aortic dissection. DHCA with bi-hemispheric SACP was employed, accompanied by hypothermia induction, pharmacological neuroprotection, and tight hemodynamic management. Postoperative outcomes were favorable, with no neurological deficits. Discussion highlights the importance of tailored acid-base, glycemic, and coagulation management strategies. Pharmacological agents, such as barbiturates and corticosteroids, show promise but require further evidence. Combining advanced monitoring techniques enhances safety and outcomes, emphasizing the need for individualized protocols to optimize DHCA efficacy and minimize complications.